1909 W.Va. Acts 479-80, ch. 60, § 19. - (:unkn) unknown (My University, 1909)
The carrying of any uncased gun in any of the fields or woods of this state, by any person not having the lawful right to hunt, pursue or kill game, birds or animals in such fields or woods shall, as to such person, other than the bona fide owner, or owners of such fields or woods, his or their child or children, tenant or tenants, lessee or lessees, be deemed prima facie evidence of a violation of this section
Keywords: CARRY; HUNTING REGULATION